2020
DOI: 10.1007/s00402-020-03412-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coronal splits on the structural stability of bi-condylar tibial plateau fractures: a biomechanical investigation

Abstract: Introduction Surgical treatment of bi-condylar tibial plateau fractures is still challenging due to the complexity of the fracture and the difficult surgical approach. Coronal fracture lines are associated with a high risk of fixation failure. However, previous biomechanical studies and fracture classifications have disregarded coronal fracture lines. Materials and methods This study aimed to develop a clinically relevant fracture model (Fracture C) and compare its mechanical behavior with the traditional Horw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Samsami et al found that coronal plane fracture lines significantly affect the mechanical response of tibial implant structures, especially medially, through their study [29]. Yet, this type of fracture models was not distinguishable by Schatzker classification.…”
Section: Discussionmentioning
confidence: 93%
“…Samsami et al found that coronal plane fracture lines significantly affect the mechanical response of tibial implant structures, especially medially, through their study [29]. Yet, this type of fracture models was not distinguishable by Schatzker classification.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, two other members of the research group questioned the relevance of fracture fragmentation because, in their personal experience, most of the PNFs were simple 2 fragment fractures. However, most of the members of the research group were in agreement that fracture morphology and fragmentation must be considered relevant because they affect primary fracture stability [ 24 , 25 ] and guide the fixation technique (i.e., the choice between relative or absolute stability) [ 26 ]. For example, the intrinsic stability and the difficulty in obtaining nail-periosteum contact in femoral spiral fractures make mandatory the use of locked nails or plates [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…One reason for the current controversy regarding the ideal fixation method for bicondylar tibial plateau fractures is related to the inadequacy of previous fracture classifications and fracture models in representing clinical morphology of the fracture site. 9,26 In clinical studies, there is no consistency about types and positions of plates used for fracture management. Therefore, applying the coronal fracture model, developed and evaluated in our institution, 9,26 we compared 2 kinds of double locked plating techniques with different positions of the medial locking plates.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Mechanical performance of osteosynthesis constructs was characterized with static and dynamic global stiffness, IFM, relative rotations of fracture fragments, survival rates, failure load, and failure cycles, which all of them were defined in our previous publication. 26 The fixation methods were statistically compared using independent t tests with a significance level of P , 0.05. The Kaplan-Meier survival analyses with log-rank tests were also used to evaluate the effects of fixation methods on sample survival rates during the fatigue test (IBM SPSS Statistics 19, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%